Fc-receptor Dependent Platelet Aggregation Induced by Monoclonal Antibodies against Platelet Glycoprotein Ib or von Willebrand Factor - Cauwenberghs, Nancy; Schlammadinger, Agotha; Vauterin, Stephan; Cooper, Susan; Descheemaeker, Gretel; Tornai, Istvan; Deckmyn, Hans (Thrombosis and Haemostasis, 2001)
In this paper we describe two pathways leading to platelet activation by crosslinking glycoprotein (GP) Ib to the platelet Fc-receptor (FcγRII). First the monoclonal antibody (MoAb) 9C8, raised against human platelet GPIbα, dose-dependently induced platelet aggregation of citrate-anticoagulated platelet-rich plasma, an effect that can be inhibited by several activation inhibitors. The FcγRII-inhibitory MoAb IV.3 was able to prevent the aggregatory effects of MoAb 9C8, indicating that crosslinking of the antigen GPIbαto the FcγII-receptor is necessary for the activating effect. Secondly we observed a synergistic activating effect of two anti-von Willebrand factor (vWF) MoAbs 1C1E7 and B724, both known to enhance vWF binding to GPIbαin the presence of shear or ristocetin. When these antibodies are added together to PRP, platelet aggregation is induced without further need for an additional modulator. This effect can be blocked by either MoAb IV.3 or an inhibitory anti-GPIbαMoAb, indicating that again the platelet activation results from signaling through FcγRII crosslinked to vWF bound to GPIbα. In addition, both the anti-GPIbαMoAb 9C8, or the two anti-vWF MoAbs 1C1E7 and B724 induce genuine platelet activation, as evidenced by the secretion of ATP and protein tyrosine phosphorylation. These findings with both anti-GPIbαand anti-vWF MoAbs add further proof to recent reports demonstrating an interaction between the platelet receptors GPIbαand FcγRII, suggesting a role for the FcγII-receptor in GPIb-related signaling.
Keywords: Monoclonal antibody; von Willebrand factor; glycoprotein Ib; FcγII-receptor; platelet activation